2005
DOI: 10.1007/s00213-005-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

Medication screening for smoking cessation: a proposal for new methodologies

Abstract: The clinical validity of short-term screening studies may improve if these studies simulate some clinical trial procedures within practical limitations. Thus, they should recruit smokers motivated to abstain, emphasize smoking abstinence as a primary index of medication response, examine effects over sufficiently long time periods to encompass the drug's mechanism of action, and assess responses in the natural environment. Whether these changes improve the sensitivity of screening studies is testable. Other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
106
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 62 publications
4
106
0
Order By: Relevance
“…For example, nicotine patch did not signifi cantly reduce total withdrawal, consistent with other studies of briefl y abstinent smokers not trying to quit permanently ( Teneggi et al, 2002 ; see also Perkins, Stitzer, & Lerman, 2006 ) but contrary to most clinical trial results ( Jorenby, Keehn, & Fiore, 1995 ). Moreover, analyses of abstinence effects by time of day were limited to the participants who self-selected to abstinence during the patch weeks, as with all cessation studies, including all outpatient and some inpatient studies of enforced abstinence (since not all are able to abstain even when paid to do so; e.g., Juliano, Donny, Houtsmuller, & Stitzer, 2006 ).…”
Section: Discussionsupporting
confidence: 86%
“…For example, nicotine patch did not signifi cantly reduce total withdrawal, consistent with other studies of briefl y abstinent smokers not trying to quit permanently ( Teneggi et al, 2002 ; see also Perkins, Stitzer, & Lerman, 2006 ) but contrary to most clinical trial results ( Jorenby, Keehn, & Fiore, 1995 ). Moreover, analyses of abstinence effects by time of day were limited to the participants who self-selected to abstinence during the patch weeks, as with all cessation studies, including all outpatient and some inpatient studies of enforced abstinence (since not all are able to abstain even when paid to do so; e.g., Juliano, Donny, Houtsmuller, & Stitzer, 2006 ).…”
Section: Discussionsupporting
confidence: 86%
“…The smokers in the study were also non-treatment seeking, which could feasibly limit the study's real-world validity. However, others have found that monetary compensation is an effective alternate reinforcer in providing motivation to resist smoking (Perkins et al, 2006;Gilbert et al, 1999), andMcKee et al (2012) found that treatment seeking status did not affect performance on this lapse task. Furthermore, the smoking cues (i.e., cigarettes and lighter) that are presented during the McKee paradigm may limit the ability of this task to identify risk factors that are predictive of lapse in the real-world.…”
Section: Discussionmentioning
confidence: 90%
“…Although this study was conducted using a double blind procedure for alcohol content, a no-alcohol beverage control should be included in future research to control for possible expectancy effects. Third, subjects were not treatment seeking which has been a criticism of laboratory studies examining various smoking cessation medication effects (see Perkins et al 2006). However, money was provided as an alternative reinforcer in order to provide some incentive for not smoking and to enhance the likelihood that the effects of alcohol on the relative reinforcing value of tobacco would be detected (see Higgins, 1997;Rodefer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, money was provided as an alternative reinforcer in order to provide some incentive for not smoking and to enhance the likelihood that the effects of alcohol on the relative reinforcing value of tobacco would be detected (see Higgins, 1997;Rodefer et al, 1997). Perkins et al (2006) and others (Stitzer et al, 1986;Gilbert et al, 1999) acknowledge that motivation to abstain can be temporarily raised through the use of monetary reinforcement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation